A longitudinal study of the psychological impact of the COVID-19 pandemic on frontline perioperative healthcare staff in an Australian tertiary public hospital. (April 2022) - Ng, Irene; Barson, Elizabeth; Fisher, Caroline; Segal, Reny; Williams, Daryl L; Krieser, Roni B; Mezzavia, Paul M; Lee, Keat; Chen, Yinwei; Sindoni, Teresa; Xu, Jessica; Lamb, Karen; et al.
Objective: This longitudinal study examined changes in psychological outcomes of perioperative frontline healthcare workers at one of Australia's most COVID-19 affected hospitals, following the surge and decline of a pandemic wave. Method: A single-centred longitudinal online survey was conducted between 26 May and 17 November 2020. Recruitment was via poster advertisement and email invitation. The survey was sent out every 4 weeks, resulting in seven time-points. Results: In total, 385 survey results were analysed from 193 staff (about 64% response rate), 72 (37%) of whom completed the survey more than once. The prevalence of moderate-to-severe anxiety and depressive symptoms peaked at 27% and 25%, respectively, during the pandemic surge. Up to 35% displayed post-traumatic stress disorder (PTSD) symptoms. Although not statistically significant, the trend of depressive and PTSD symptoms worsened over time, especially among females and anaesthetic/surgical trainees, despite subsidence of the pandemic curve. Technicians and anaesthetic/scrub nurses were the at-risk groups with worst psychological outcomes. Conclusion: We found persistent mental health impacts on frontline perioperative HCWs despite subsidence of the pandemic wave. Further research is needed to determine the extent and trajectory of such impacts with larger sample sizes to determine generalisability to frontline HCWs in general.